Comparison between deep intracornual artificial insemination (dIAI) and conventional artificial insemination (AI) using low concentration of spermatozoa in beef cattle - Meirelles,Ciro (2012)
This study aimed to compare the pregnancy rate using the conventional artificial insemination (AI) or deep intracornual artificial insemination (DIAI), with low number of spermatozoa (4.0 million sperm) in 270 Nelore cows. The animals were divided in two groups (G: G1 (135 cows) conventional AI was performed (=semen deposition in the uterine body) and in G2 (135 cows) to DIAI, in ipsilateral horn where the dominant follicle in the ovary had previously been detected, by ultrasound examinations. For both the methods, a single artificial insemination was carried out after visual estrus observation, checked three times a day (morning, afternoon and evening). The pregnancy diagnosis after 45 days was conducted by ultrasound. Results showed a better pregnancy rate in the DIAI group (67.4% - p<0.01), when compared to conventional AI (48.8%) with low spermatozoa concentration.